Thermodynamic and physical properties of Zr3Fe and ZrFe2 intermetallic compounds. (June 2019) - Mukhamedov, B.O.; Saenko, I.; Ponomareva, A.V.; Kriegel, M.J.; Chugreev, A.; Udovsky, A.; Fabrichnaya, O.; Abrikosov, I.A.
Abstract: Experimental differential scanning calorimetry measurements and ab-initio simulations were carried out to define the heat capacities of Zr3 Fe and C15-ZrFe2 compounds from 0 K up to their maximum stability temperatures. Experimental measurements of heat capacity of each compound were performed for the first time in wide range of temperatures. Density functional theory and quasi-harmonic approximation (QHA) were employed to calculate the free energy of the studied systems as a function of volume and temperature. A good agreement was observed between theoretical and experimental heat capacities within validity range of the QHA. This makes it possible to combine theoretical and experimental data to determine the standard entropies of intermetallic compounds. Highlights: DFT calculations of thermodynamic properties of Zr3 Fe and ZrFe2 in range 0–300 K. Effect of finite-temperatures was described within quasi-harmonic approximation. Heat capacities at constant volume C V and pressure C P were calculated. Heat capacity of the Zr3 Fe was measured for the first time from 100 to 1023 K. Heat capacity of the ZrFe2 was measured in the range from 100 K to 1473 K.